2015
DOI: 10.1097/ico.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Patient and Clinician Assessment of Dry Eye Severity and Treatment Response in Taiwan

Abstract: There were marked differences in the degree of DED severity and treatment response between patient and clinician assessment. Clinicians may underestimate DED severity and persistence of dry eye symptoms after treatment with artificial tears.Clinical Trial Registration-URL: http://www.clinicaltrials.gov. Unique identifier: NCT01942226.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Thus, there may be some disconnect between clinical assessment of “effectiveness” and patients’ perception of “relief” associated with current medications use. Patient- and physician-reported assessments of DED severity often diverge and, despite reports of patient experience being positively associated with clinical effectiveness, contrary reports of patient experience often being not in concordance with clinical assessments also exist [28, 29]. The fact that symptoms, causes and especially treatments of DED are most frequently discussed in the context of their impact on patients’ lives in the current study, points to the practical concerns that are most bothersome to patients; these may differ from clinical measures of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may be some disconnect between clinical assessment of “effectiveness” and patients’ perception of “relief” associated with current medications use. Patient- and physician-reported assessments of DED severity often diverge and, despite reports of patient experience being positively associated with clinical effectiveness, contrary reports of patient experience often being not in concordance with clinical assessments also exist [28, 29]. The fact that symptoms, causes and especially treatments of DED are most frequently discussed in the context of their impact on patients’ lives in the current study, points to the practical concerns that are most bothersome to patients; these may differ from clinical measures of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the severity between symptoms and signs of dry eye may be inconsistent in this study. Yeh et al 44 demonstrated a low agreement between clinicians and patient assessments in dry eye severity, which may explain the inconsistency. Because the results of the differences between groups and before and after treatment are inconsistent in some parameters, it is hard to make a strong conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Based on OSDI score, the ocular surface is defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe (33-100) [44]. It is noteworthy that although the OSDI is not routinely used in clinical practice, it has been shown to be valid and reliable to quantify the impact of dry eye on the quality of life [44].…”
Section: Discussionmentioning
confidence: 99%